PENERAPANPEMBELAJARAN M-APOS DENGAN SIKLUS ADL DALAM MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL CERITA PADA MATERI VOLUME KUBUS DAN BALOK DI KELAS VIII E SMPN 7 JEMBER SEMESTER GENAP TAHUN AJARAN 2012/2013 - Wahyuningtyas, Desi; Pambudi, Didik Sugeng; Trapsilasiwi, Dinawati (Kadikma, 2014)
Abstract: The research aims to know the application of M-APOS for overcome student’s mistakes aboutvolume of cube and cuboidtopic at eight grade of juniorhigh school. M-APOS is development of APOS theory. M-APOS using ACE teaching cycle that consists of three components: activities, classroom discussion, and exercises. The subject of research is students of VIII E class SMPN 7 Jember in even semester academic year 2012/ 2013. The kinds of student’s mistakes consist of error using data, error of theorem or definition, technical errors, and another mistakes. This research design is Classroom Action Research (CAR) and the method of data collecting using observation, interview, test and documentation. The result of research indicate that the result of learning activity increase of student’s activity of cycle I reach 82,2% and cycle II reach 85,8%. While the student’s mistakes at cycle I reach 17,4% and cycle II 8,55%. So, the mode of teaching can increase student’s activity and decrease the student’s mistakes. Key Words: M-APOS, cube and cuboid,, student’s activity, student’s mistakes